The Use of Non-Comparative Figure of Speech in The Snack Advertisements on Indonesian Television as The Learning Materials in School - Fitrah, Rizka Amalia; Juita, Novia (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This study aims to develop the theory of linguistics and find out the use of the figures speech contained in snack advertisements and to assist students in achieving the optimal learning objectives so that they are proficient in determining themes, using appropriate diction and figure of speech and interesting forms of writing in writing advertisement. This was a qualitative study using descriptive methods. The research data were in the form of advertisement texts spoken by the advertising stars and the line's slogan. Data were collected by using the method of listening to the note-taking technique. An interactive analysis model was used to analyze the data. The data validation in the form of a triangulation technique was used in this study. The findings showed that there were thirty advertisements for snacks and one hundred and forty-five data containing non-comparative figures of speech. The most dominant type of non-comparative figure of speech was ninety-seven hyperboles. Thus, it can be concluded that there are several important things from the research results, namely the use of other figures of speech, the form of a figure of speech, and the meaning of non-comparative figures of speech in snack advertisements on Indonesian television.